Sistem Kompensasi Karyawan Banquet Kitchen Pada Hotel Double Tree By Hilton Jakarta Bintaro Jaya (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
The compensation system is an important element in human resource management, because it plays a direct role in influencing employee motivation, performance, and job satisfaction. In human resource management, the existence of human resources plays a vital role that must be considered by the company, including in terms of compensation. The ideal compensation system is one based on the principles of fairness and appropriateness, which can be directly felt by employees. The assessment of fairness and appropriateness can be seen from several dimensions, namely the internal dimension relating to the suitability of workload and rewards received, the external dimension considering company policies and market standards, and the individual dimension relating to the ability of compensation to meet employee living needs. Based on this, this study focuses on the compensation system implemented at the Double-Tree By Hilton Bintaro Jaya Hotel, specifically for banquet kitchen staff consisting of contract staff and daily workers. This study uses a descriptive qualitative approach with data collection through interviews, observations, and documentation. The results show that the compensation system for contract staff has been running optimally. From the internal side, the workload is considered commensurate with the rewards received. Externally, the compensation provided is competitive compared to competing companies. Furthermore, from an individual perspective, employees' living needs are met, even supported by a substantial service charge that exceeds their base salary. However, for daily workers, the compensation system is deemed suboptimal. Although their workload is equivalent to that of contract staff, their compensation is not the same, and they do not receive a service charge. Based on these findings, this study recommends optimizing the compensation system, particularly for daily workers, to ensure fairness and equity across all staff levels, thereby increasing work motivation, loyalty, and overall performance.